Analisis Literasi Matematis Siswa SMP di Kabupaten Lebak-Banten: Studi Kasus Soal Tipe PISA dengan Memperhatikan Faktor Akreditasi, Status Sekolah, Tingkat Kemampuan, dan Jenis Kelamin - Yulianto, Dwi; Umami, Moh Rizal; Junaedi, Yusup; Anwar, Syahrul (PAKAR Pendidikan, 2024)
This article examines the level of students' abilities in solving PISA-type questions. Since Indonesia joined in 2000, the country's achievements have consistently been at a lower level in the PISA index. With a consistent ranking at the bottom of the PISA index, Indonesia faces the consequence of the perception that its education system does not meet global standards and is below that of other countries. This research aims to provide an overview of the mathematical literacy skills of junior high school students in solving PISA-type questions in Kabupaten Lebak-Banten, considering factors such as school accreditation, school status, student proficiency levels, and gender. This survey research involved 667 eighth-grade junior high school students in Kabupaten Lebak, Banten. The data analysis technique used includes descriptive and inferential statistics. The findings of this research include: 1) there are differences in the mathematical literacy skills of junior high school students in solving PISA-type questions in Kabupaten Lebak-Banten based on school accreditation, 2) there is no difference in the mathematical literacy skills of junior high school students in solving PISA-type questions in Kabupaten Lebak-Banten between public and private schools, 3) differences in the mathematical literacy skills of junior high school students in solving PISA-type questions in Kabupaten Lebak-Banten based on students' proficiency levels, 4) there is no difference in the mathematical literacy skills of junior high school students in solving PISA-type questions in Kabupaten Lebak-Banten between male and female students.